Formative Assessment in Nepalese Secondary Level English Classrooms: Tactics, Engagement and Responses (SNPRC Journal, 2024)
Formative assessment supports learning, and in Nepalese school education, it is emphasized in the curriculum but inconsistently practiced in classrooms. In this context, this study explores the formative assessment strategies that secondary-level English language teachers apply in the classroom in Nepal. It also examines how teachers engage students with these strategies and how students experience these formative assessment practices in community schools. To achieve the research objectives, four English language teachers and twelve students from community schools in the Kathmandu Valley were selected using purposive sampling. The study employed an interpretative phenomenological analysis design. Data were collected through class observations and interviews with both teachers and students. The data were analyzed and interpreted descriptively by identifying themes. The findings revealed that most teachers use classwork and homework as formative assessment strategies. Peer correction, group correction, teacher correction, and self-correction were commonly used to engage students in formative assessment activities. The majority of students responded positively to the formative assessment strategies their teachers used and the way they were engaged in the processes. It implies that incorporating diverse formative assessment strategies can effectively engage students and foster positive attitudes toward learning.